On the Matter of Dynamic Optimality in an Extended Model for Tree Access Operations - Fredman, Michael L. (Algorithms and Data Structures, 2011)
The model of node access operations taking place in binary search trees subject to rotations is extended to unordered binary trees, as motivated by consideration of certain self-adjusting priority queues. Rotations in this extended model can be preceded by sibling subtree swaps. Whereas the Wilber lower bound for off-line computation extends to this model of computation – a precondition for the possibility of dynamic optimality – the goal of dynamic optimality is nonetheless demonstrated to be unattainable in this model.